Localized (1)H NMR Spectroscopy in Different Regions of Human Brain In Vivo at 7 T: T(2) Relaxation Times and Concentrations of Cerebral Metabolites - Marjańska, Małgorzata (2011)
At the high field strength of 7 T, in vivo spectra of the human brain with exceptional spectral quality sufficient to quantify sixteen metabolites have previously been obtained only in the occipital lobe. However, neurochemical abnormalities associated with many brain disorders are expected to occur in brain structures other than the occipital lobe. The purpose of the present study was to obtain high quality spectra from various brain regions at 7 T and to quantify the concentrations of different metabolites. To obtain concentrations of metabolites within four different regions of the brain such as occipital lobe, motor cortex, basal ganglia, and cerebellum, the T(2) relaxation times of the singlets and J-coupled metabolites in these regions were measured for the first time at 7 T. Our results demonstrate that high quality, quantifiable spectra can be obtained in regions other than the occipital lobe at 7 T utilizing a 16-channel transceiver coil and B(1)(+) shimming.